Effect of different dietary energy and protein sources on antioxidant status, fresh yolk fatty acid profile and microstructure of salted yolks in laying ducks. (8th January 2018) - Ruan, D.; Hu, Y. J.; Fouad, A. M.; Lin, C. X.; Xu, Z. P.; Chen, W.; Fan, Q. L.; Xia, W. G.; Wang, S.; Wang, Y.; Yang, L.; Zheng, C. T.
Abstract : The study investigated whether different dietary energy and protein sources affect laying performance, antioxidant status, fresh yolk fatty acid profile and quality of salted yolks in laying ducks. In all, 360 19-week-old Longyan ducks were randomly assigned to four diets in a factorial arrangement (2×2). The four diets consisted of two energy sources, corn (CO) or sorghum (SO) and two protein sources, soybean meal (SM) and rapeseed meal with corn distillers dried grains with solubles (RMD), and each treatment contained six replicates of 15 birds each. The experimental diets were isocaloric (metabolizable energy, 10.84 MJ/kg) and isonitrogenous (CP, 17%). The results showed that egg production, average egg weight, egg mass and feed conversion ratio were not affected by diets ( P >0.05). Plasma contents of reduced glutathione (GSH), GSH/oxidized glutathione and total antioxidant capacity were lower ( P <0.05) in ducks fed the RMD diets compared with those fed SM diets with a substantial increase ( P =0.006) in plasma content of malondialdehyde (MDA). Egg yolks from ducks fed SO diets had higher proportions of polyunsaturated fatty acids (PUFA) and lower saturated and monounsaturated fatty acids compared with CO diets ( P <0.001). Similarly, ducks fed RMD diets had a higher content of PUFA and n-6/n-3 ratio in fresh yolks ( P <0.001), and increased salted yolk MDA, carbonylated proteins content and incidence of hard salted yolks ( P <0.05) compared with SM diets. Scanning electron microscopy showed that salted yolks contained rougher polyhedral granules and fewer fat droplets, and were surrounded with a layer of bunchy fibers in ducks fed SO+RMD than those fed CO+SM diet. In conclusion, the current study showed that feeding laying ducks with diets containing SO or RMD reduced antioxidant capacity and increased egg yolk concentrations of PUFA. It appeared that egg yolks from ducks fed these diets were more sensitive to lipid peroxidation and protein oxidation during salting, and reduced the quality of salted yolks.